Willingness to pay for wholesome canteen takeaway - Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2011)
The primary objective of this study was to estimate the willingness to pay (WTP) for a new intervention at the workplace: wholesome canteen takeaways (CTA), i.e. a low fat meal with a large amount of vegetables prepared at the workplace canteen that only requires re-heating. The contingent valuation method was used to elicit the WTP. Two surveys were carried out in Denmark; one large-scale Internet based survey and one survey at a workplace that introduced CTA. The results from the large-scale survey suggest that this concept attracts relevant target groups; groups of individuals with a less healthy diet, low physical activity and a high body mass index. For males and individuals with low education, who also constitute relevant target groups, the results suggest no significant difference in WTP between males and females, whereas low educated individuals have a significantly lower WTP than highly educated individuals. However, the workplace study, carried out at a hospital, found that females have a significantly higher WTP for CTA compared with males. In conclusion, the concept appears to attract relevant target groups, although for a given price a smaller fraction of low educated individuals compared to high educated individuals would be willing to buy CTA.
Keywords: D12; I10; 330; Workplace intervention; healthy; contingent valuation; diet; willingness to pay; fast food; takeaway meal; demand